Blade runner the director's cut - Shaw, Run Run 1907-; Yorkin, Bud 1926- (The Blade Runner Partnership, 1991)
Los Angeles, 2019: Deckard, an expert "blade runner," must identify and execute four replicants, genetically engineered beings virtually identical to humans, which have illegally returned to earth from their off-world slave duty.